Cathepsin B-mediated Autophagy Flux Facilitates the Anthrax Toxin Receptor 2-mediated Delivery of Anthrax Lethal Factor into the Cytoplasm - Ha, Soon-Duck (American Society for Biochemistry and Molecular Biology, 2010)
Anthrax lethal toxin (LeTx) is a virulence factor secreted by Bacillus anthracis and has direct cytotoxic effects on most cells once released into the cytoplasm. The cytoplasmic delivery of the proteolytically active component of LeTx, lethal factor (LF), is carried out by the transporter component, protective antigen, which interacts with either of two known surface receptors known as anthrax toxin receptor (ANTXR) 1 and 2. We found that the cytoplasmic delivery of LF by ANTXR2 was mediated by cathepsin B (CTSB) and required lysosomal fusion with LeTx-containing endosomes. Also, binding of protective antigen to ANXTR1 or -2 triggered autophagy, which facilitated the cytoplasmic delivery of ANTXR2-associated LF. We found that whereas cells treated with the membrane-permeable CTSB inhibitor CA074-Me- or CTSB-deficient cells had no defect in fusion of LC3-containing autophagic vacuoles with lysosomes, autophagic flux was significantly delayed. These results suggested that the ANTXR2-mediated cytoplasmic delivery of LF was enhanced by CTSB-dependent autophagic flux.